TOURISM COMPETITIVENESS, TOURIST FOREIGN ARRIVAL AND NON-TAX STATE REVENUE IN NATIONAL PARKS IN INDONESIA - Eddyono, Fauziah; Darusman, Dudung; Sumarwan, Ujang; Sunarminto, Tutut (Association of Indonesian Forestry and Environment Researchers and Technicians, 2022)
Indonesia has a natural tourist attraction in the form of 54 national parks spread across regencies and cities, with an area of 16,304,707.13 hectares, featuring a diversity of ecosystems, high mountains, lowlands, savannahs to wetlands, and waters. However, the appeal of natural tourism does not necessarily contribute to the performance of national tourism, hence studies need to support of increase in tourist arrivals to national parks, one of which is to study tourism competitiveness in areas that have national parks in Indonesia. This research aims to develop a model of tourism competitiveness management in areas that have national parks in Indonesia. The theory underlying this research is the theory of tourism competitiveness through the approach of the competitiveness index of the Travel & Tourism Competitiveness Index, Indicators for Measuring Competitiveness in Tourism, and Competitiveness Monitor. The research design uses 20 competitiveness factors, where data collection techniques utilize data that has been available at both government and non-government institutions and the data collection method uses library research. The data were analysed by using the dynamic model method. The results of the study found that tourist arrivals significantly correlated simultaneously with the factor of tourism competitiveness of the districts and cities that have national parks, tourist arrival, revenue tourism, and conservation in zona utility of national park in Indonesia. It is proposed that local governments, national parks management and other interested parties make policy innovations to optimize the factors of tourism competitiveness in their regions to support or increase in the number of tourist visits in national parks